Modification of g-C3N4 with metal oxides for high catalytic degradation of methylene blue and phenol in aqueous solution - He, J.; Liu, S.; Sun, Hongqi; Wang, Shaobin (CHEMECA, 2015)
A series of metal doped graphitic carbon nitride (Fe2O3-g-C3N4, Fe3O4-g-C3N4 and MnO2-g-C3N4) photocatalysts were synthesized using a hydrothermal method. The catalytic performances of these materials were evaluated in liquid-phase heterogeneous activation of peroxymonosulfate (PMS) for decomposition of phenol and photocatalytic degradation of methylene blue (MB) under UV-vis light irradiation. Their physicochemical properties were characterized by X-ray diffraction (XRD), UV-vis diffusion reflectance spectroscopy, Fourier transform infrared spectroscopy (FTIR), and thermogravimetric analysis (TGA). The experimental results showed that MnO2-g-C3N4 exhibited higher activity than Fe2O3-g-C3N4and Fe3O4-g-C3N4 in photodecomposition of organic compounds in liquid phase. It was found that the physical and optical properties of g-C3N4 have changed upon metal deposition. Manganese ions had a significant effect on the structure and catalytic performance of g-C3N4 and the enhanced photocatalytic activity of MnO2-g-C3N4 can be attributed to the large heterojunction interface and intrinsically layered structure.